IMPROVING KNOWLEDGE OF BIDAI CLOTHES IN STUDENTS THROUGH EMERGENCY TRAINING - Rolly Rondonuwu; Maykel A. Kiling; Christine Siwi (Jurnal Ilmiah Perawat Manado (Juiperdo), 2018)
Background: According to WHO it is estimated that 70% of traffic accidents are experienced by students. Based on data from the Asian Development Bank, traffic accidents in Indonesia claimed 37,000 lives in 2005 and 48,000 in 2010. The types of injuries or injuries sustained as a result of traffic accidents are 49% or bruising injuries, 65.9% abrasions, open injuries 26.7, burns 1.9%, sprained 21%, broken bones 8.5 and broken 1.0% limb (WHO, 2007), Injury due to traffic accidents will increase in 2020 and will be the third leading cause of death in the world after coronary heart disease and depression (Hutapea, 2012). Objective: This study aims to determine the Effect of Bandage, Nursing and Evacuation Training on Student Knowledge in Emergency Management in Adventahan High School. Method: This type of research is a pre-experimental design study using one group pre-post design test design to compare knowledge before and after training in splint and evacuation. The study population was 45 students. The sampling technique used is the sample used is simple random sampling, which is as many as 30 students. Results: Analysis by Wilcoxon test. The results of the test have a significant effect on the training of bandaging, aids and evacuation (α ≤ 0.05 ie p-value = 0.000). The conclusion of this study is that there is a significant influence on the training of wrapping, aids and evacuation of students' knowledge in emergency management in Advent Ratahan High School. Suggestions to broaden students' knowledge about first aid dressing and evacuation, it is better for Adventahan High School to be an extracurricular school act. Keywords: Bandage training; aids and evacuation disaster